2022
DOI: 10.1021/acs.inorgchem.2c01452
|View full text |Cite
|
Sign up to set email alerts
|

2D/2D CsPbBr3/BiOCl Heterojunction with an S-Scheme Charge Transfer for Boosting the Photocatalytic Conversion of CO2

Abstract: The rational design of a two-dimensional (2D)/2D "face-to-face" heterojunction photocatalyst is crucial for the mediation of interfacial charge transfer/separation. Herein, a unique 2D/2D step-scheme (S-scheme) photocatalyst of CsPbBr 3 /BiOCl is constructed by the self-assembly of CsPbBr 3 and BiOCl nanosheets (NSs). Profiting from the effective interface contact and appropriate band structures between CsPbBr 3 and BiOCl NSs, a valid S-scheme heterojunction of CsPbBr 3 /BiOCl is established. Density functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…The C dl values of Ni 3 B and TiO 2 are, respectively, 28.86 and 14.37 μF cm –2 , while the optimized Ni 3 B/TiO 2 had an improved C dl value of 34.19 μF cm –2 , indicating that the introduction of Ni 3 B can provide a larger electrochemically active surface area and more active sites, which greatly improve the activity of photocatalytic CO 2 reduction . The mechanism of interfacial electron transfer in semiconductor heterojunctions can be further studied by calculating the work function (Φ), which is derived from the difference between the vacuum energy level ( E V ) and the Fermi energy level ( E F ) of the semiconductor by DFT calculations. As shown in Figure , the work functions of TiO 2 (101) and Ni 3 B­(102) surfaces are, respectively, calculated as 6.93 and 5.14 eV, indicating that the Fermi energy level of Ni 3 B is much lower than that of TiO 2 , which leads to the transfer of electrons excited in TiO 2 to the surface of Ni 3 B under the interfacial electric field when they are in close contact, which remains consistent with the analysis of XPS results. , …”
Section: Resultsmentioning
confidence: 99%
“…The C dl values of Ni 3 B and TiO 2 are, respectively, 28.86 and 14.37 μF cm –2 , while the optimized Ni 3 B/TiO 2 had an improved C dl value of 34.19 μF cm –2 , indicating that the introduction of Ni 3 B can provide a larger electrochemically active surface area and more active sites, which greatly improve the activity of photocatalytic CO 2 reduction . The mechanism of interfacial electron transfer in semiconductor heterojunctions can be further studied by calculating the work function (Φ), which is derived from the difference between the vacuum energy level ( E V ) and the Fermi energy level ( E F ) of the semiconductor by DFT calculations. As shown in Figure , the work functions of TiO 2 (101) and Ni 3 B­(102) surfaces are, respectively, calculated as 6.93 and 5.14 eV, indicating that the Fermi energy level of Ni 3 B is much lower than that of TiO 2 , which leads to the transfer of electrons excited in TiO 2 to the surface of Ni 3 B under the interfacial electric field when they are in close contact, which remains consistent with the analysis of XPS results. , …”
Section: Resultsmentioning
confidence: 99%
“…Of note, from XPS analysis we confirmed the formation of the UCN/Nb 2 O 5 -(2) and Pt/UCN/Nb 2 O 5 -(2) heterostructures and, based on the changes in binding energies, we could say that positive changes in binding energy correspond to lower electron density, while negative changes in binding energy correspond to higher electron density. 41,42 Therefore, the observed positive shifts in the C 1s and N 1s spectra of UCN/Nb 2 O 5 -(2) and Pt/UCN/Nb 2 O 5 -(2), along with the negative shifts in the Nb 3d spectra of UCN/Nb 2 O 5 -(2) and Pt/UCN/Nb 2 O 5 -(2) compared with UCN, firmly underpinned the electron transfer from UCN to Nb 2 O 5 in the heterostructure. This was further validated by EPR analysis and is discussed in the section on mechanistic studies.…”
Section: Resultsmentioning
confidence: 87%
“…However, its relatively large band gap of 3.3 eV inhibits visible-light utilization. , In this regard, combining g-C 3 N 4 with ZnO could benefit the photocatalytic performance since low-band gap g-C 3 N 4 could produce excited charge carriers and transfer to catalytically more reactive ZnO. In particular, it has been reported that the g-C 3 N 4 /ZnO heterostructure exhibits significantly enhanced photocatalytic performance for hydrogen production and dye degradation under visible-light irradiation. , A computational study reported that strain-induced g-C 3 N 4 /ZnO heterostructures offer suitable band edge positions and improved electron–hole separation. , …”
Section: Introductionmentioning
confidence: 99%